A high temperature reduction cleaning (HTRC) process: a novel method for conductivity recovery of yttrium-doped barium zirconate electrolytes. Issue 27 (23rd June 2016) - Han, Donglin; Iihara, Junji; Uemura, Shigeaki; Kazumi, Kenji; Hiraiwa, Chihiro; Majima, Masatoshi; Uda, Tetsuya
Abstract : A novel high temperature reduction cleaning (HTRC) process to recover the electrical conductivity of Y-doped barium zirconate electrolytes from Ni contamination. Abstract : Proton conducting Y-doped BaZrO3 (BZY) and nickel oxide (NiO) are currently the most promising electrolyte and anode catalyst for protonic ceramic fuel cells, respectively. However, during the co-sintering process to fabricate the fuel cells, Ni cations diffuse from the anode into the lattice of the BZY electrolyte, resulting in significant degradation of the electrolyte conductivity and fuel cell performance. With the aim to solve such a problem, in this work, we report a novel method, named as high temperature reduction cleaning (HTRC) process, which is composed of several sequential heat-treatments in controlled atmospheres. The most interesting point is that after heat-treating the NiO-contaminated BZY at 1400 °C in a Ti-deoxidized Ar atmosphere for 100 h, Ni cations were observed to be expulsed from the BZY lattice and segregated at the grain boundary as Ni metal particles. And the conductivity of the BZY electrolyte was recovered. However, delamination along the grain boundary of the BZY electrolyte was introduced when the segregated Ni metal particles were oxidized to NiO particles in an oxygen atmosphere. And a series of sequential heat-treatments were designed to solve such a problem.